Encounters with problems and challenges and the formal complaints mechanism in public health: Accounts and perceptions of a set of junior health professionals during early employment experience - Petersen, Wendy (Department of Sociology, 2020)
The South African health system consists of partly privatized and partly public health care. It is the latter that is responsible for the wellbeing of the majority of the South African population. It is also the latter however that faces multiple challenges. Of these are challenges relating to working hours, staff to patient ratio, and burnout, as well as the availability of resources / equipment; supervision and training and the experiences of bullying. Moreover, research shows that while the working conditions / contexts as well as the availability of supervision that junior healthcare professionals work in and have access to has been studied extensively in both Northern and Southern literature; the bullying experienced by junior doctors and other junior health professionals have been extensively studied in Western literature with very little being done to study this phenomenon. Further, very little has been done to study questions pertaining to the mechanisms of laying complaints about these challenges in the South. Against this background, the thesis was concerned to explore experiences and perceptions of laying complaints to supervisors and the largest health regulatory body in South Africa, the Health Professions Council of South Africa (HPCSA). The thesis used semi-structured interviews to interview six junior healthcare professionals who are registered and thus regulated by the HPCSA in South Africa and who are in the process of or who have recently completed their compulsory year/s of internship / community service in any public hospital in South Africa. This was done in order to explore their accounts and perceptions of challenges and complaints mechanisms pertaining to these challenges in their first postgraduate years. The public health system in South Africa is still rife with many challenges. My research found that according to their own accounts, junior healthcare workers encounter these as direct challenges in their everyday experience. They bear the brunt of these by having to deal with major burnout associated with long working hours and understaffing. It also shows that their account is that there is a lack of much needed resources and equipment and that challenges associated with this often have dire consequences for both them and their patients. Further, my research showed that they continue to feel that they are not being properly trained and supervised and that they do indeed face many challenges relating to bullying behavior by senior health professionals. Connected to this, my research showed that despite being aware of the complaints mechanisms in place, these junior healthcare workers often have had negative experiences with laying complaints and / or have negative perceptions about complaint mechanisms such as their supervisors and the HPCSA. In sum, the findings show that these challenges sustain and exacerbate each other in a vicious cycle in South Africa. While the sample used in this research was based in issues of access and availability and is not representative, these patterns and themes emerged consistently and thus warrant further investigation both in themselves and as possibly representative of what is happening in the medical profession in South Africa.